Editorial - Fernández-Arata, Manuel (2021)
Liberabit, Revista Peruana de Psicología is pleased to share with the national and international academic community, seven research articles corresponding to the first issue of volume 27 of this year. We begin this presentation with the work of Nelson Castro, Ximena Suárez and Enrique Barra, who examine the relationship of emotional regulation difficulties and personality variables with life satisfaction in Chilean university students, finding that they are significantly associated; also, that responsibility and neuroticism are predictors of life satisfaction, highlighting the importance of the ability to deal with emotions and accept them in the educational process. Alejandro Emilio Pagano and Nicolás Alejandro Vizioli evaluated the temporal stability and discriminant validity of the Beck Anxiety Inventory in Argentine participants, reporting evidence of good temporal stability, since error sources do not significantly affect the scores, as well as an adequate discrimination capacity, mainly to be able to distinguish anxiety from depression.